A Summation Formula Clung to Contiguous Relation (Global Journal of Science Frontier Research, 2013)
The main aim of the present paper is to evaluate a summation formula in the shadow of contiguous relation and recurrence relation.
Keywords: gaussian hypergeometric function; contiguous function; recurrence relation; bailey summation theorem and legendre duplication formula